EVALUATING COMPLIANCE OF CONSTRUCTION SITE SAFETY RULES AS A COMPLIMENTARY TOOL TO PROJECT COMPLETION WITHIN BUDGET LIMIT - CHUKWUEMEKA, ENEOGWE INNOCENT; MICHAEL UDUMA, OKOR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The Systematic flow process necessary for a successful delivery of building project requires the collective wisdom of the construction team. Thus making construction site a very busy and dangerous place to work in due to the manifold of work items going on simultaneously. Owing to the risk inherent in construction sites, this study focuses on the evaluation of compliance to safety rules on construction sites that can serve as complementary tools in completing a building project within the budget. A project that is not completed on or within the budget limit is an indication of poor quality administration of construction process. The study adopts the focus group techniques to observe that inadequate safety protocols can increase insurance costs as a result of worker’s compensation claims and law suits due to construction site accidents. The following were among the very quality result oriented construction sites safety rules. Wearing of Personal Protective Equipment (PPE) like the Hi-vis Vest, ear muffs and hard hats at all times, keeping a tidy site and prompt report of defective equipment. Not only does safety on construction sites protect workers, it also keeps the public safe and consequently helps to maintain the construction cost within approved limit.